2005
DOI: 10.1016/j.febslet.2005.09.095
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide induces tau hyperphosphorylation via glycogen synthase kinase‐3β activation

Abstract: Nitric oxide is associated with neurofibrillary tangle, which is composed mainly of hyperphosphorylated tau in the brain of AlzheimerÕs disease (AD). However, the role of nitric oxide in tau hyperphosphorylation is unclear. Here we show that nitric oxide produced by sodium nitroprusside (SNP), a recognized donor of nitric oxide, induces tau hyperphosphorylation at Ser396/404 and Ser262 in HEK293/tau441 cells with a simultaneous activation of glycogen synthase kinase-3b (GSK-3b). Pretreatment of the cells with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 39 publications
(45 reference statements)
1
26
0
1
Order By: Relevance
“…This resulted in a significant GSK3b dephosphorylation and massive loss of BsB8 cells in monolayer cultures. Of interest, SNP which is clinically approved antihypertensive agent (Cheng et al, 2005), and serves as a donor of nitric oxide, has been also found as a potent GSK3b activator (Zhang et al, 2005). In this respect, recent reports have shown a strong SNP-mediated cytotoxicity against different tumor cell lines in vitro (Blackburn et al, 1998;Chao et al, 2004), and our study also has demonstrated its effectiveness, in combination with IGF-IR inhibition, against otherwise resistant human medulloblastoma cell line, D384 (Figure 7).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This resulted in a significant GSK3b dephosphorylation and massive loss of BsB8 cells in monolayer cultures. Of interest, SNP which is clinically approved antihypertensive agent (Cheng et al, 2005), and serves as a donor of nitric oxide, has been also found as a potent GSK3b activator (Zhang et al, 2005). In this respect, recent reports have shown a strong SNP-mediated cytotoxicity against different tumor cell lines in vitro (Blackburn et al, 1998;Chao et al, 2004), and our study also has demonstrated its effectiveness, in combination with IGF-IR inhibition, against otherwise resistant human medulloblastoma cell line, D384 (Figure 7).…”
Section: Discussionsupporting
confidence: 50%
“…The SNP treatment has recently been found to cause the dephosphorylation of the serine 9 residue of GSK3b (Zhang et al, 2005). Indeed, results in Figure 6c indicate that the presence of SNP efficiently decreased GSK3b phosphorylation at this site.…”
Section: Igf-ir-gsk3b Signaling Interaction In Medulloblastomamentioning
confidence: 73%
“…Moreover, NO induces tau hyperphosphorylation via GSK3β activation [21]. The inactivation of GSK3β has been shown to correlate with reduced degeneration in vivo [38].…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of GSK3β has been shown to induce apoptosis through the activation of caspase-3 [19][20][21]. We investigated the levels of GSK3β activity by its phosphorylation status.…”
Section: High No Levels Reduce Self-renewal Of Nscs Through Activatiomentioning
confidence: 99%
“…Excessive NO production by iNOS is also a contributory factor in the onset of septic shock [9]. Over active nNOS can result in hyperphosphorlyation and accumulation of tau proteins, an event which has been implicated in Alzheimer's disease [24,25]. In addition oxidative damage caused by over active nNOS leads to dysregulation of the signalling pathways and has long been associated with a variety of neurological conditions including Parkinson's disease [26,27].…”
Section: Nos and Diseasementioning
confidence: 99%